Pengaruh Storytelling Marketing, Kemudahan Penggunaan Marketplace Dan Diskon Terhadap Minat Beli Mahasiswa Kota Denpasar Pada Marketplace Shopee - Desak Gede Cistani Surya Putri; Kadek Adyatna Wedananta (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2025)
This study aims to analyze the influence of Storytelling Marketing, ease of use of the Marketplace, and discounts on the purchase intention of students in Denpasar City on the Shopee Marketplace. The research is motivated by the increasing e-commerce transactions driven by digital marketing strategies and attractive promotions. The study employs a quantitative survey method, collecting data through questionnaires from 150 active students using Shopee. Data analysis is conducted using multiple linear regression to examine the effects of independent variables on purchase intention as the dependent variable. The results show that Storytelling Marketing positively and significantly affects purchase intention (β = 0.236; p < 0.05), ease of use of the Marketplace also has a positive and significant effect (β = 0.364; p < 0.05), and discounts positively and significantly influence purchase intention (β = 0.159; p < 0.05). Simultaneously, these three variables significantly affect students’ purchase intention with F = 18.333; Sig. = 0.000 and Adjusted R² = 0.597, indicating that 59.7% of the variation in purchase intention can be explained by these variables. This study supports the Theory of Planned Behavior (TPB), suggesting that positive attitudes, perceived behavioral control, and external incentives collectively shape strong purchase intentions. In conclusion, storytelling-based marketing strategies, platform usability, and discount provision collectively increase students’ purchase intention on the Shopee Marketplace.